THE CORRELATION STUDY ABOUT POSITIVE THINKING AND BEHAVIOR FORGIVENESS AMONGS STUDENTS - Fahmi, Reza; Jamaldi, Jamaldi; Fulnandra, Dila (JURNAL AL-AQIDAH, 2020)
The purpose of this study was to determine the category of positive thinking , the category of forgiving behavior and to determine the  relationship of positive thinking with Forgiveness Behavior in friendship at Heler boarding school students. The research method used quantitative methods with data analysis techniques, namely Pearson Correlation analysis . The population in this study amounted to 78 people with a sample of 65 people. The sampling technique used was stratified random sampling . The data collection technique used in this study was a psychological scale, which was guided by a modified Likert scale , namely a positive thinking scale and a forgiving behavior Thus H o rejected and H a accepted, meaning that positive thinking with a forgiving behavior in friendship at the boarding students heler in Lubuk Leeches have a positive and significant relationship.